2013
DOI: 10.1093/icvts/ivt132
|View full text |Cite
|
Sign up to set email alerts
|

The STS score is the strongest predictor of long-term survival following transcatheter aortic valve implantation, whereas access route (transapical versus transfemoral) has no predictive value beyond the periprocedural phase

Abstract: The STS score outperforms the logistic EuroSCORE in predicting adverse outcomes following TAVI. The transapical approach is associated with higher perioperative mortality, but does not exert any influence on long-term prognosis beyond the periprocedural phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 21 publications
3
45
1
1
Order By: Relevance
“…23 A recent report from another European registry demonstrated that early hazard of death was higher after TA-TAVR than TF-TAVR, but the long-term prognosis was equivalent. 24 As experience with patient selection and performing TA-TAVR grew, early mortality and complications diminished. 21 Whether further improvement is achievable with other anatomic approaches such as direct transaortic is unknown.…”
Section: Differences In Outcomementioning
confidence: 99%
“…23 A recent report from another European registry demonstrated that early hazard of death was higher after TA-TAVR than TF-TAVR, but the long-term prognosis was equivalent. 24 As experience with patient selection and performing TA-TAVR grew, early mortality and complications diminished. 21 Whether further improvement is achievable with other anatomic approaches such as direct transaortic is unknown.…”
Section: Differences In Outcomementioning
confidence: 99%
“…We gave priority to the STS score if both scores were available as it has been demonstrated to be superior to Euroscore in predicting outcomes (16,17). STS predicted risk of mortality (PROM) (mean <8%) was used as a benchmark for inclusion on the basis of the SURTAVI definition of the intermediate risk categories.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…While Stahli et al 16 in a cohort of 350 patients and Sedaghat et al 15 in a cohort of 206 patients demonstrated the superiority of EuroSCORE II, Hemmann et al 17 in a record of 426 patients considered the STS superior. Other studies, as well as our work, demonstrated no difference between the scores, and, in our case, both the EuroSCORE II and STS scores had the ability to predict mortality, with AUC of 0.77 and 0.81, respectively.…”
Section: Discussionmentioning
confidence: 99%